FORMATION OF A CLUSTER BUSINESS MODEL BASED ON MARKETING PRINCIPLES - Nehoda, Serhii F. (Journal of Strategic Economic Research, 2025)
The purpose of the article is formation of a cluster business model based on marketing principles. The article presents the results of a study on the formation of a cluster business model on a marketing basis. It is substantiated that an effective tool for reforming the cluster business development management system can be a proactive management system, which is built on the analysis of past, identified current and possible future errors, and the timely formation of management business decisions on this basis, the creation of cluster models for effective implementation. The implementation of the marketing principle of proactive management requires the creation of a mobile organizational structure for cluster management, which would be flexible, dynamic; quickly adapt to unforeseen changes in external conditions; would have the ability to self-organize individual links as the task changes. It is established that the mechanism of state guarantees of investment projects should include assistance to innovative cluster business through insurance of investment risks in high-tech industries and the provision of guarantees to investors. Special attention should be paid to state stimulation of the investment process at all levels, the formation of a certain trust in the economic policy of the state. The smooth implementation of the proposed developments is possible under the conditions of introducing a regional-functional structure of the organization of cluster business management on the basis of marketing, which is characterized by the possibility of effective goods movement (due to an integrated, diversification direction), small branching and a clear division of duties and responsibilities.